Recent Developments on Phenstatins as Potent Antimitotic Agents - Chen, Xing; Wang, Shi-Meng; Kumar, Gajjela B.; Bare, Grant A.L.; Leng, Jing; Bukhari, Syed N. A.; Qin, Hua-Li (Current Medicinal Chemistry, 2018)
Background: Phenstatin and their derivatives display remarkable antiproliferative activity toward a wide variety of preclinical tumor models. Structural simplicity and excellent stability of phenstatins offer a stimulating premise for developing various derivatives with profound antimitotic activity and excellent cytotoxicity. Objective: To do analysis of literature that phenstatins derivatives inhibit tubulin polymerization through their interaction at the colchicine binding site of microtubules and arrest the G2/M phase of the cell cycle. In addition, phenstatin derivatives are undergoing clinical evaluation as vascular targeting/disrupting agents and also exhibit direct antiangiogenic properties. Methods: An organised well designed and appropriately managed search of bibliographic databases for peer-reviewed research literature using a focused review question and inclusion/ exclusion criteria has been done for this article. Conclusion: In this review article, the synthesis and structure-activity relationships of phenstatin and a wide number of their reported analogues with modifications to ring A, ring B, and to the keto position are discussed in the perspective of medicinal chemistry with proper conclusion.
Keywords: Colchicine binding site